2023
DOI: 10.1177/02655322221145643
|View full text |Cite
|
Sign up to set email alerts
|

Linking scores from two written receptive English academic vocabulary tests—The VLT-Ac and the AVT

Abstract: The academic section of the Vocabulary Levels Test (VLT-Ac) and the Academic Vocabulary Test (AVT) both assess meaning-recognition knowledge of written receptive academic vocabulary, deemed central for engagement in academic activities. Depending on the purpose and context of the testing, either of the tests can be appropriate, but for research and pedagogical purposes, it is important to be able to compare scores achieved on the two tests between administrations and within similar contexts. Based on a sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Other studies found that both vocabulary knowledge can accurately represent participants' language competency is a stronger indication of such competency (González-Fernández, 2022;Rivera Perez, 2019). It is crucial to define these terms and emphasize their significance when addressing formal or academic vocabulary for English language learners (Cooper, 2000;Crosson et al, 2019;Warnby, 2022aWarnby, , 2022b. Furthermore, in the following table, concerning the creativity aspect in learning vocabulary.…”
Section: Note: 1=never; 2= Sometimes; 3 =Usually; 4= Often; 5=alwaysmentioning
confidence: 98%
“…Other studies found that both vocabulary knowledge can accurately represent participants' language competency is a stronger indication of such competency (González-Fernández, 2022;Rivera Perez, 2019). It is crucial to define these terms and emphasize their significance when addressing formal or academic vocabulary for English language learners (Cooper, 2000;Crosson et al, 2019;Warnby, 2022aWarnby, , 2022b. Furthermore, in the following table, concerning the creativity aspect in learning vocabulary.…”
Section: Note: 1=never; 2= Sometimes; 3 =Usually; 4= Often; 5=alwaysmentioning
confidence: 98%
“…Although the multiple-choice format is potentially vulnerable to guessing or other test-taking strategies, e.g., [51], it can nevertheless be a useful tool in this context since it encourages participants to pick the most likely option based on the resources they have available to them, including partial knowledge or recognition of cognates, which is relevant when investigating vocabulary acquisition through incidental learning. It should be noted that there are limitations inherent in the design of the VST, such as the small sampling rate [52] and the fact that the test is based on word families rather than lemmas, which may give more accurate estimates of vocabulary size [53,54], and therefore, vocabulary size estimates based on this test should be interpreted with caution.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…Although the multiple-choice format is potentially vulnerable to guessing or other test-taking strategies, e.g., [51], it can nevertheless be a useful tool in this context since it encourages participants to pick the most likely option based on the resources they have available to them, including partial knowledge or recognition of cognates, which is relevant when investigating vocabulary acquisition through incidental learning. It should be noted that there are limitations inherent in the design of the VST, such as the small sampling rate [52] and the fact that the test is based on word families rather than lemmas, which may give more accurate estimates of vocabulary size [53,54], and therefore, vocabulary size estimates based on this test should be interpreted with caution. Since previous research [13] found that university students in Norway enrolled in English programs demonstrated a high level of mastery of the most frequently occurring 5000 words in English, only the items from the 5000 level of the VST and up to the maximum of 14,000 words were included in the current study in order to reduce participant fatigue and increase chances of completion of the survey.…”
Section: Participants and Proceduresmentioning
confidence: 99%